Quarter-Life Crisis and Religious Conversion Intention among Generation Z Social Media Users: The Moderating Role of Religiosity - Tri Cahyaning Utami; Hidayatus Salehah; Patimah Patimah; Nor Alini; Surawan Surawan (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
The development of digital technology and social media has reshaped how Generation Z constructs identity, including religious identity. During emerging adulthood, individuals often face social pressure, future uncertainty, and intensive identity exploration, which may trigger a quarter-life crisis characterized by anxiety, confusion, and emotional instability. In this condition, some individuals engage in spiritual exploration and may consider religious conversion as a way to seek meaning, certainty, and psychological stability. This study aimed to examine the relationship between quarter-life crisis and religious conversion intention among Generation Z social media users, as well as the moderating role of religiosity in this relationship. A quantitative survey design was employed using purposive sampling. The participants consisted of social media users aged 18–29 years. Data were analyzed using regression and moderation analysis. The findings indicated that quarter-life crisis did not have a significant direct effect on religious conversion intention. However, religiosity had a positive and significant effect and moderated the relationship between quarter-life crisis and conversion intention. Specifically, religiosity weakened the association between psychological crisis and the tendency to consider religious conversion, suggesting its role as a protective factor in maintaining religious identity stability under psychological pressure. These findings imply that religious commitment may help Generation Z manage identity uncertainty and emotional instability in the digital era. This study contributes to the literature on emerging adulthood, religious identity, and social media by highlighting the psychological and spiritual mechanisms underlying religious conversion intention. Practically, the findings underscore the importance of strengthening religious guidance, digital literacy, and psychosocial support for young adults experiencing identity-related crises.